(3GdJYGhf GdEbJUGOj GdYQHj hCaGb GdeSJbHd (B/s - (3CMeO, CMeO jhSas; (3GdfGHdSj, eMeO SYjO hCNQhfs ((3YeGf(B: s (3eQcR GdHfc GdYQHj GdYdej(B, s, 2001)
(3GdEWGQ GdSjGSj ddJYGhf GdYQHj(B- (3NhGWQ Mhd OhQ GdefXeGJ GdMchejI GdYQHjI GdYGedI aj eLGd GdYdGbGJ GdEbJUGOjI(B- (3GdEJaGbjGJ GdYQHjI GdKfGFjI hCKQgG Ydi GdJYGhf GdEbJUGOj GdYQHj(B- (3GdEUdGM GdEOGQj hCKQg aj GdJYGhf GdEbJUGOj GdYQHj(B- (3GdJYGhf GdEbJUGOj GdYQHj aj Xd GdHjFI GdeDSSI GdYGdejI(B- (3efWbI GdJLGQI GdYQHjI GdMQI GdcHQi (B-(3GdEecGfGJ hGdhSGFd(B- (3GdJfSjb hGdJYGhf Hjf GdHfhc GdeQcRjI hCKQgG Ydi GdEbJUGO GdYQHj(B- (3OhQ GdeUGQa GdYQHjI hCKQg Ydi GdEbJUGO GdYQHj(B- (3OhQ bWGY GdNGU aj GdJfejI GdEbJUGOjI GdYQHjI(B- (3GdeYdheGJjI hOhQgG aj JMbjb GdJYGhf GdEbJUGOj GdYQHjs
Keywords: (3GdEbJUGO GdOhdjs; (3GdEbJUGO GdYQHjs; (3GdJcGed GdEbJUGOjs